CHARTING A NEW PATH FOR POLAND OR TURNING ITS BACK ON MORE THAN A QUARTER CENTURY OF PROGRESS? - Hunter, Richard J. (Archives of Business Research, 2017)
The paper analyzes the Morawiecki Plan for the Polish economy in light of its emphasis on encouraging domestic, rather than foreign, development in Poland. It discusses the critique of the current government relating to foreign ownership of assets in Poland and what the government intends to do about reversing this trend from both historical and practical perspectives. The paper includes both positive and negative assessments of these proposed changes in policy and emphasis.